Demographics and Outcomes of Initial Phase of COVID-19 Medicines Delivery Units Across 4 UK Centers During Peak B1.1.529 Omicron Epidemic: A Service Evaluation. (6th October 2022) - Brown, Michael; Saund, Jasjot; Qureshi, Azka; Plowright, Megan; Drury, Katie; Gahir, Joshua; Simpson, Tom; Newman, Thomas; Adams, Kate; Galloway, James; Durairaj, Kezia; Elgizouli, Kamla; et al.
Abstract: Background: COVID-19 medicines delivery units (CMDU) were established in late December 2021 to deliver early antiviral therapy to patients classified as at risk with the aim of preventing hospitalization. Methods: We performed a service evaluation at 4 CMDUs in England. We assessed demographics and triage outcomes of CMDU referral, uptake of antiviral therapy, and the rate of subsequent hospitalizations within 2 weeks of CMDU referral. Results: Over a 3-week period, 4788 patients were referred and 3989 were ultimately assessed by a CMDU. Overall, 832 of the patients referred (17%) were judged eligible for treatment and 628 (13%) were ultimately prescribed an antiviral agent. The overall rate of admission within 14 days was 1%. Patients who were admitted were significantly older than those who did not require hospitalization. Of patients prescribed molnupiravir and sotrovimab, 1.8% and 3.2%, respectively, were admitted. Conclusions: There was a high volume of referrals to CMDU service during the initial surge of the Omicron wave in the United Kingdom. A minority of patients were judged to be eligible for therapy. In a highly vaccinated population, the overall hospitalization rate was low. Abstract : In a multi-centre study we found most patients with COVID-19 referred for consideration of anti-viral therapy ultimately were not eligible for therapy. In a highly vaccinated population the overall rate of admission was low.